Anisotropy Across Fields and Scales - Özarslan, Evren; Schultz, Thomas; Zhang, Eugene; Fuster, Andrea (Mathematics and Visualization, 2021)
This open access book focuses on processing, modeling, and visualization of anisotropy information...